Find the series expansion of $\left(e^{(x-1)}\right)^2$. I thought maybe I could use binomial expansion but that is only for $(1+x)^n$, so now I am unsure how to proceed. I could set $(x-1)^2=n$ and use the series expansion for $e^n$.

  • $\begingroup$ do you mean $e^{((x-1)^2)}$ or $(e^{(x-1)})^2$ $\endgroup$ – Jimmy R. Oct 22 '14 at 16:27

Since it is unclear whether you mean $e^{\left((x-1)^2\right)}$ or $\left(e^{(x-1)}\right)^2$, I consider both cases: $$e^{\left((x-1)^2\right)}=\sum_{n=0}^{\infty}\dfrac{\left((x-1)^2\right)^n}{n!}=\sum_{n=0}^{\infty}\dfrac{(x-1)^{2n}}{n!}$$ but $$\left(e^{(x-1)}\right)^2=e^{(x-1)+(x-1)}=e^{2(x-1)}=\sum_{n=0}^{\infty}\dfrac{\left(2(x-1)\right)^n}{n!}$$

The second term can be also written as $$\left(e^{(x-1)}\right)^2=e^{2(x-1)}=e^{-2}\cdot e^{2x}=e^{-2}\cdot\left(1+\dfrac{2}{1!}x^1+\dfrac{2^2}{2!}x^2+\dfrac{2^3}{3!}x^3+\dfrac{2^4}{4!}x^4+\ldots\right)$$ which is the Taylor expansion of the function $f(x)=e^{2x}$ at $a=0$.

  • $\begingroup$ I meant the second one, (e^(x−1))^2, do you have any idea how to find that from basic series expansions, not just by using the formula? $\endgroup$ – user183782 Oct 22 '14 at 16:37
  • $\begingroup$ See my edit above $\endgroup$ – Jimmy R. Oct 22 '14 at 16:45
  • $\begingroup$ @user183782 Use the binomial theorem on $\lim_{n\to\infty}(1+\frac xn)^n$ to get the Taylor expansion of $e^x$. $\endgroup$ – Akiva Weinberger Oct 22 '14 at 18:20

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.